STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN PENDAPATAN WARUNG PONDOK BAKSO MINI DI DESA PENINJAUAN KECAMATAN MARO SEBO ULU - Vevi Andriani; Rafidah Rafidah; Ferri Saputra Tanjung (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
This study aims to (1) find out the sharia marketing strategy in increasing income carried out by mini meatball cottage traders in the review village of Maro Sebo Ulu sub-district. (2) To find out the obstacles faced in an effort to increase the income of mini meatball stalls. This research uses descriptive qualitative method. Data collection techniques in this study are using observation techniques, interviews and documentation. The theory used in this study is the theory put forward by Abuznaid to formulate the definition of sharia marketing, namely, wise decisions in order to satisfy customer needs through good behavior, presenting healthy products or services (halalan thoyyibah) with the approval of both parties (seller and buyer). ) in order to achieve material and spiritual welfare, the world and the hereafter through an ethical world. In addition to the theory used by Kotler, marketing is a way in which companies involve consumers, build good relationships with consumers and create value for consumers, so as to get good value or response from consumers in increasing profits and consumer feedback. The 4P marketing strategies used are product, price, place, and promotion. The results of this study indicate that the marketing strategy carried out by Pondok Meatball Mini in increasing income with product strategies ranging from improvement of the quality of the products served, product health, product hygiene and product halalness Pricing strategy, mini meatball huts have set affordable, relatively cheap prices, the prices offered by these mini meatball huts are affordable and cheap according to the economy of the review village community and suitable for all walks of life teenagers and adults. The strategy of location, pondok mini meatball stalls prioritizes the cleanliness of the place and the comfort of consumers while at the pondok mini meatball stalls. promotion strategy, pondok mini meatball stalls do not promote through social media, only do word of mouth promotion, but not a few who already know the existence of these mini meatball stalls. while the income earned by mini meatball cottages is still relative or fluctuating, depending on the crowd of visitors.